2021
DOI: 10.1042/cs20210790
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and obesity: endotoxin another insult to add to injury?

Abstract: Low-grade inflammation is often an underlying cause of several chronic diseases such as asthma, obesity, cardiovascular disease, and type 2 diabetes mellitus (T2DM). Defining the mediators of such chronic low-grade inflammation often appears dependent on which disease is being investigated. However, downstream systemic inflammatory cytokine responses in these diseases often overlap, noting there is no doubt more than one factor at play to heighten the inflammatory response. Furthermore, it is increasingly beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 236 publications
(228 reference statements)
0
8
0
Order By: Relevance
“…51 Occludin and ZO-1 help sustain the gut barrier integrity and protect normal gut permeability. Recently, it was suggested that low-grade inflammation is often an underlying case of metabolic dysfunction including obesity, type 2 diabetes mellitus, and cardiovascular disease, 52 and modulating the gut microbiota serves as a therapeutic intervention for diabets. 53 Therefore, targeting H. pylori may be a potential for early intervention for prevention of ADrelated MD.…”
Section: H Pylori In the Gutmentioning
confidence: 99%
“…51 Occludin and ZO-1 help sustain the gut barrier integrity and protect normal gut permeability. Recently, it was suggested that low-grade inflammation is often an underlying case of metabolic dysfunction including obesity, type 2 diabetes mellitus, and cardiovascular disease, 52 and modulating the gut microbiota serves as a therapeutic intervention for diabets. 53 Therefore, targeting H. pylori may be a potential for early intervention for prevention of ADrelated MD.…”
Section: H Pylori In the Gutmentioning
confidence: 99%
“…Numerous factors, such as endotoxin and pro-inflammatory cytokines, have been linked to the disease’s pathogenesis ( Zhou M. et al, 2019 ; Kessoku et al, 2021 ; Lad et al, 2021 ). Host immunity, resulting in the release of pro-inflammatory cytokines and activation of the excessive immune cascade, is accompanied by significant liver damage in the early stages of ACLF ( Liu, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Th2 phenotype is generally harder to control, and it reacts to the treatment with more poor results. A non-Th2 phenotype of severe asthma, which occurs because of a neutrophil immune response, is also related to the resistance to corticosteroids, which complicates selection of a treatment scheme [ 27 ].…”
Section: Resultsmentioning
confidence: 99%